Apakah Pertumbuhan Ekonomi mampu berjalan beriringan dengan Keberlanjutan Lingkungan? - Melti Roza Adry; Dewi Zaini Putri; Tiara Aprilia Putri Hernanda (Jurnal Ecogen, 2023)
The influence of human activity on the environment is becoming one of the world's significant problems. This arises because of growing concerns about the influence of each country's economic activity on the global environment. On the other hand, sustainable economic growth and human well-being are recognized as dependent on the benefits derived from the environment. This study aims to analyze the impact of economic growth on environmental quality in Indonesia.  To analyze the impact, regression analysis of polynomial panels was used by using panel data from 34 provinces in Indonesia in 2014 – 2019. The results found that non-linear GDP per capita only had a significant effect on the quality of land cover and water quality in Indonesia, but it did not have a significant effect on air quality. As for provinces in Java and Bali, it was found that non-linear GDP per capita only had a significant effect on air quality and land cover but did not have a significant effect on water quality in the area. Unlike provinces outside Java and Bali, GDP per capita non-linearly has a significant effect on air and water quality, but it does not have a significant effect on land cover quality. These results provide different recommendations for each  regional cluster.